Caracterización morfométrica y clasificación de los espermatozoides de vicuña (Vicugna vicugna) usando el sistema ISAS® CASA-Morph - Cucho, Hernán; Puelles, Olger; Meza, Aydee; Urquizo, Darwin; Coila, Leonidas; Valverde-Abarca, Anthony (Spermova, 2021)
he aim of the study was to determine the morphological and morphometric characteristics of the vicuña sperm (Vicugna vicugna), looking for possible subpopulations in its structure. Semen was collected by electroejaculation method from three adult male vicuñas weighing 50.33 ± 2.52 kg, once per animal. The volume, color and concentration, sperm morphology and morphometry were determined. The samples for the analysis of sperm morphology and morphometry were stained with Hemacolor®, and analyzed using the CASA-Morph, Integrated Semen Analysis System (ISAS®v1). Five forms of the vicuña sperm head were distinguished: normal, piriform, long, short and rounded. The morphometric parameters determined were the length, width, area, perimeter, ellipticity, elongation, regularity and rugosity of the vicuña sperm head, percentage of acrosome, head gray level, as well as the width, area, distance and angle of insertion of midpiece of the sperm. In relation to morphology, significant differences (P <0.05) were found in the percentage distribution of head shapes, with the normal shape (55.7%) being the majority and different from the other shapes. Significant differences (P <0.05) were found between animals in the morphometric variables of head, percentage of acrosome, ellipticity, rugosity, elongation and gray level; while the variables of the midpiece and regularity did not show differences (P> 0.05). The morphometric variables were distributed in four main components (PCA) called elongation, area, circularity and midpiece width, which explained 84.59% of the total variance. The cluster analysis determined five subpopulations (SP): SP1 grouped small cells of low length, width and area (18.8%); SP2 of sperm of large size, both in area and width of the head (17.38%); SP3 of rounded cells with high values of percentage of acrosome and head gray level (24.04%); SP4 of spermatozoa of intermediate size and elongated, with greater ellipticities and elongation (23.61%); and SP5 of cells of intermediate size and short, with low values of area and length (16.71%)

El objetivo del estudio fue determinar las características morfológicas y morfométricas del espermatozoide de vicuña (Vicugna vicugna), buscando posibles subpoblaciones de acuerdo con su estructura. Se colectó semen por el método de electroeyaculación de tres vicuñas machos adultos con un peso de 50.33 ± 2.52 kg, en una oportunidad por animal. Se determinó el volumen, color y concentración, la morfología y morfometría espermática. Las muestras para el análisis de la morfología y morfometría espermática, fueron teñidas con Hemacolor®, y analizadas utilizando el sistema CASA-Morph, Integrated Semen Analysis System (ISAS®v1). Se distinguió 5 formas de la cabeza del espermatozoide de vicuña: normal, piriforme, larga, corta y redondeada. Los parámetros morfométricos determinados fueron la longitud, anchura, área, perímetro, elipticidad, elongación, regularidad y rugosidad de la cabeza del espermatozoide de vicuña, porcentaje de acrosoma, nivel de gris, así como la anchura, área, distancia y ángulo de inserción de la pieza intermedia del espermatozoide. En relación con la morfología, hubo diferencias significativas (P< 0.05) en la distribución porcentual de formas de la cabeza, siendo a forma normal (55.7%) la mayoritaria y diferente a las otras formas. Se encontraron diferencias significativas (P< 0.05) entre animales en las variables morfométricas de cabeza, porcentaje de acrosoma, elipticidad, rugosidad, elongación y nivel de gris; mientras que las variables de la pieza intermedia y regularidad no mostraron diferencias (P>0.05). Las variables morfométricas, se distribuyeron en cuatro componentes principales (PCA) denominados elongación, área, circularidad y anchura de la pieza intermedia, y explicaron un 84.59% de la varianza total. El análisis de clústeres determinó cinco subpoblaciones (SP): SP1 agrupó células pequeñas de baja longitud, anchura y área (18.8%); SP2 de espermas de tamaño grande, tanto en área y anchura de la cabeza (17.38%); SP3 de células redondeadas con valores altos de porcentaje de acrosoma y nivel de gris (24.04%); SP4 de espermatozoides de tamaño intermedio y alargadas, con mayores elipticidades y elongación (23.61%); y SP5 de células de tamaño intermedio y cortas, con valores bajos de área y longitud (16.71%).
Spermova, vol.11, no.2 (dic, 2021):115-123
Keywords: Vicuña; Espermatozoides; Anatomía comparada; Casa Morph -- Programa para computador